The modified 200 keV pulsed electron beam source for the VEPP-5 injection complex - Akimov, A.V.; Akimov, V.E.; Bak, P.A.; Kazarezov, I.V.; Korepanov, A.A.; Kulenko, Ya.V.; Ribitskaia, T.V.; Kuznetsov, G.I.; Pachkov, A.A.; Tiunov, M.A. (Вопросы атомной науки и техники, 2006)
The modified pulsed electron beam source on voltage 200 kV and current 10 A with half-height pulse duration 2.5 ns and repetition rate 50 Hz is described. The source gun has been performed on the base of impregnated cathode with 20 mm diameter. The cathode pulse voltage is formed by storage capacitance discharge through IGBT switch and pulse transformer. The gun control unit located at the high voltage potential produces cathode heat voltage and control grid voltage. The source test results are presented.